2010
DOI: 10.5423/ppj.2010.26.1.017
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Regression Analysis to Determine Infection Models of Colletotrichum acutatum Causing Anthracnose of Chili Pepper Using Logistic Equation

Abstract: A logistic model for describing combined effects of both temperature and wetness period on appressorium formation was developed using laboratory data on percent appressorium formation of Colletotrichum acutatum. In addition, the possible use of the logistic model for forecasting infection risks was also evaluated as compared with a first-order linear model. A simplified equilibrium model for enzymatic reactions was applied to obtain a temperature function for asymptote parameter (A) of logistic model. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…They explained that climate change would affect the optimal conditions for infection, host specificity, and mechanisms of plant infection. Plant pathogens are strongly affected by environment; therefore, the survival, rate of multiplication, vigor, sporulation, direction, distance of dispersal of inocula, rate of spore germination, and penetration of pathogens can be affected in the climate-change scenario (Kang et al, 2010). The authors suggested that climate-induced changes would affect the measures farmers use to effectively control diseases and the viability of particular cropping systems in particular regions.…”
Section: Potential Effects Of Climate Change On Pestsmentioning
confidence: 99%
“…They explained that climate change would affect the optimal conditions for infection, host specificity, and mechanisms of plant infection. Plant pathogens are strongly affected by environment; therefore, the survival, rate of multiplication, vigor, sporulation, direction, distance of dispersal of inocula, rate of spore germination, and penetration of pathogens can be affected in the climate-change scenario (Kang et al, 2010). The authors suggested that climate-induced changes would affect the measures farmers use to effectively control diseases and the viability of particular cropping systems in particular regions.…”
Section: Potential Effects Of Climate Change On Pestsmentioning
confidence: 99%
“…X is an independent variable, usually representing the effect of weather. Kang et al (2010) have estimated the percentage of appressorium formation of the fungus Colletotrichum acutatum, the causal agent of anthracnose of chili pepper, using a multiple linear regression model as follows: P = -13.3 + 0.612T + 0.928W where: P = percentage of appressorium formation; T = level of temperature (°C); W = period of wetness (h).…”
Section: Static Models the First Step Towards A Quantitative Approachmentioning
confidence: 99%
“…Hot pepper ( Capsicum annum L.) is cultivated on more than 55,000 ha in Korea and is one of the country’s most important cash vegetable crops ( Kim, 2010 ). Pests of hot pepper can cause severe damage to yields ( Kang et al, 2010 ; Myung et al, 2009). Its diseases include anthracnose ( Colletotrichum acutatum J. H. Simmonds), Phytophthora blight ( Phytophthora capsici Leonian), bacterial wilt ( Ralstonia solanacearum (Smith) Yabuuchi et al), and bacterial spot ( Xanthomonas campestris pv.…”
mentioning
confidence: 99%
“…Each program has a critical model for advising the proper time to treat hot peppers with pesticides. The anthracnose infection model calculates a cumulative infection risk (IR) value every hour based on the hourly temperature and moisture characteristics ( Ahn et al, 2008 ; Huber and Gillespie, 1992 ; Kang et al, 2010 ; Wilson et al, 1990 ). The tobacco budworm program has a population model which calculates the cumulative eclosion rates for the first and second generations based on the degree-day model to control eggs and the younger stages of larvae, respectively ( Jung, 2010 ).…”
mentioning
confidence: 99%